A Guitarra Elétrica em Gruppen Für Drei Orchester Karlheinz Stockhausen - Mariano, Anderson de Sousa (2011)
This researsh analyses the participation of the electric guitar in the work Gruppen für drei orchester of the German composer Karlheinz Stockhausen. The work is subdivided in three chapters. The first deals history aspects of the instrument and its use in the avantgarde concert music of the twentieth century, featuring a selection of works of the most important composers of this aesthetics, in which the electric guitar participates. In the second chapter, the focus are the general aspects related to the work and the composer, in addiction to a deepening in the pre compositional plan of Gruppen and in the group composition technique used in the work; on this the first three groups of the work are analyzed. In the third chapter, we have selected the groups in which the electric guitar is present, examining the serial context of the work, based on the main parameters instrumentation, pitchs, rhythm, articulations an dynamics, them including an explanation about the idiomatic use of the instrument in fostering of the groups sounds, and the exposure of a typing model of the electric guitar score for entire the work.